Self-assembling layers created by membrane proteins on gold. (22nd May 2007) - Shah, D.S.; Thomas, M.B.; Phillips, S.; Cisneros, D.A.; Le Brun, A.P.; Holt, S.A.; Lakey, J.H.
Abstract : Membrane systems are based on several types of organization. First, amphiphilic lipids are able to create monolayer and bilayer structures which may be flat, vesicular or micellar. Into these structures membrane proteins can be inserted which use the membrane to provide signals for lateral and orientational organization. Furthermore, the proteins are the product of highly specific self-assembly otherwise known as folding, which mostly places individual atoms at precise places in three dimensions. These structures all have dimensions in the nanoscale, except for the size of membrane planes which may extend for millimetres in large liposomes or centimetres on planar surfaces such as monolayers at the air/water interface. Membrane systems can be assembled on to surfaces to create supported bilayers and these have uses in biosensors and in electrical measurements using modified ion channels. The supported systems also allow for measurements using spectroscopy, surface plasmon resonance and atomic force microscopy. By combining the roles of lipids and proteins, highly ordered and specific structures can be self-assembled in aqueous solution at the nanoscale.